O governo Bolsonaro contra os Povos Indígenas: as garantias constitucionais postas à prova - François-Michel Le Tourneau (Confins)
The 2018 election in Brazil has allowed a ultra-conservative political force to power, leading to new challenges to Indigenous land rights in the country. Despite the warranties offered by the 1988 Constitution, the government of Jair Bolsonaro is determined to halt any new demarcation of Indigenous lands, and to shrink as much as possible the existing ones. In such an adverse political landscape for Brazil’s Indigenous peoples and their supporters, this paper is an attempt to sum up what the stakes are. We start by remembering where Brazil’s Indigenous lands are and what are the juridical grounds which sustain them. We then analyze the ideological background of the actual government regarding Indigenous peoples and the measures it has taken since January 2019. Last, we propose three more or less optimistic scenarios for the near future in which we try to identify the fracture lines